Evaluation of anti-COVID-19 measures taken by the parents of children with celiac disease: a cross-sectional study - Bükülmez, Ayşegül; Baş, Melike Taşdelen; Çiftci, Esra (São Paulo Medical Journal, 2021)
BACKGROUND: Coronavirus disease 2019 (COVID-19) causes negative life changes brought about through lockdowns, in addition to severe complications and death. Among these changes, asplenism or hyposplenism has been reported in patients with celiac disease. It has been reported that the risk of pneumococcal sepsis is higher in celiac patients with hyposplenism. Moreover, celiac patients present high risk of admission to hospital due to influenza. OBJECTIVE: To determine the degree of awareness of COVID-19 among parents of children with celiac disease and examine the measures that they take. DESIGN AND SETTING: Cross-sectional study at a university hospital in the Middle Anatolian region of Turkey. METHODS: The diagnosis of celiac disease was confirmed through a survey conducted online among 73 parents between May and July 2020. RESULTS: The mean age was 37.57 ± 6.56 years for the mothers, 41.15 ± 5.56 years for the fathers and 11.36 ± 4.36 years for the children. 90.4% of the parents reported that COVID-19 was transmitted through “speaking, coughing, sneezing and infection of the face after contact with virus-infected surfaces”. Moreover, 78.1% indicated that they did not have any difficulty in finding gluten-free foods. CONCLUSION: These parents of children with celiac disease believed that their children’s risk of developing COVID-19 did not differ from that of healthy children. It was also observed that appetite and states of nervousness were higher among these children with celiac disease during lockdowns and that their sleep patterns were affected.